Electronic Government Procurement Systems in Solving Precedent Public Procurement Problems - Komakech Kenneth Oloya (Uganda Christian University, 2023)
The study examined the Electronic Government Procurement system(E-GP) on solving procurement problems in Public Procurement drawing empirical evidence from the Ministry of Water and Environment(MoWE), Luzira Kampala Uganda. The study was based on the following study objectives: to investigate transparency under E-GP system, to investigate the efficiency of procurement processes under the E-GP system and to analyze contract management under the E-GP system in the Ministry of Water and Environment (MoWE), Luzira Kampala, Uganda. The study adopted a descriptive cross sectional survey design where both quantitative and qualitative approaches where used. In this study, a total number of 74 respondents were expected but 49 respondents returned the survey instruments representing a response rate of 79.3%. The data was collected using questionnaires and interviews and quantitative data analysis was done using Pearson correlation coefficients. Qualitative analysis was done using content and thematic analysis. Findings revealed that there is a positive significant relationship between the E-GP system and transparency in purchasing at the Ministry of Water and Environment(MoWE) at r=271*. There is a positive significant relationship between the E-GP system and efficiency in public procurement processes at r=.271* and lastly, there is a positive relationship between contract management and the Electronic Government Procurement system at r=0.786. Conclusively: The adoption and implementation of the E-GP system in the purchasing procedures in the Ministry of Water and Environment(MoWE) has significant solved its underlying procurement issues by increasing transparency in procurement activities in the entity whereby all the concerned stake holders clearly have visibility of procurement information which is availed to them on the E-GP system. The system has notably increased the efficiencies of the purchasing activities in the entity as it has significantly reduced costs and enhanced the speed of the stages associated with purchasing in the entity. The E-GP system has reduced unnecessary administrative reviews hence increasing the rate at which projects and purchasing activities are executed in the entity. The E-GP system has also embedded smart contracting in the entity as most of the important stages of the contracting process-oriented and executed on the E-GP platform.
This is a dissertation.